The relationship of health knowledge, attitude and implementation of health protocol with incidence of suspected COVID-19 on pregnant mothers at Lendah II Public Health Center - Ria Indriastuti; Heru Subaris Kasjono; Dwiana Estiwidani (Alma Ata University Press, 2022)
Background: A individual who matches one of the clinical criteria for acute fever and cough is suspected of having COVID-19. Fever, cough, weakness, headache, muscle aches, sore throat, runny nose/stuffed nose, shortness of breath, anorexia, nausea, diarrhea, or loss of consciousness are all possible symptoms or patients with severe ARI (Acute Respiratory Infection) who have had a fever (> 38°C) and cough in the last 10 days, or who have had acute anosmia, or who have had acute ageusia without other causes that have gone away.Objectives: The goal of this study was to see if there was a link between the amount of knowledge, attitudes, and application of health protocols in pregnant women at the Lendah II Health Center and the incidence of suspected covid-19. Methods: This cross-sectional survey took place from November 12, 2021, to January 31, 2022. The number of respondents in this study was 80, and the samples were gathered using a purposive sampling technique. The data collection tool employs a questionnaire sheet and the Ag-RDT screening method to examine covid-19 suspected. Univariate data analysis with frequency distribution, bivariate data analysis with chi square test, and multivariate data analysis with logistic regression were employed in this studyResults: According to the bivariate analysis, there was a 0.000 p value relationship between mothers and the results of the covid-19 screening, a 0.031 p value relationship between the mother's attitude and the results of the incidence of suspected covid-19 and a 0.005 p value relationship between the implementation of the health protocol and the results of the incidence of suspected covid-19. With a significance value of 0.000, the results of the multivariate analysis of the independent variables have a joint effect on the assessment of thi incidence of suspected covid-19. Knowledge has a OR value of 0.006, attitude is 0.196, and health-care implementation has a OR value of 0.079.Conclusions: There were correlation between of the incidence of suspected covid-19 in pregnant women at the Lendah II Health Center are linked to knowledge, attitude, and application of health protocols